Radical prescription : citizenship and the politics of tuberculosis in twentieth-century Cuba - Urban, Kelly (Chapel Hill : The University of North Carolina Press, 2023)
"In this first comprehensive study of tuberculosis in modern Cuba, Kelly Urban analyzes the medical, social, and governmental responses to the highly contagious disease, particularly as the island was heading into and emerging from the 1959 revolution. Tuberculosis--one of the top three causes of death in Cuba at the beginning of the twentieth century--provides a window onto broad questions of citizens' rights, biomedicine and public health, and political change"--
Chapter Five. A Shuttered Laboratory: Tuberculosis Policy Experiments in the Early Revolution -- Chapter Six. Therapeutic Revolution: The Boundaries of Health Citizenship under Socialism -- Conclusion. The Battleground of Health: From the Special Period to COVID-19 -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- X -- Y -- Z
Description based on online resource; title from digital title page (viewed on April 06, 2023).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Tuberculosis -- Cuba -- History -- 20th century; Public health -- Cuba -- History -- 20th century; Medical policy -- Cuba -- History -- 20th century; Cuba -- History -- 1895-; Cuba -- Politics and government -- 1895-; Tuberculose -- Cuba -- Histoire -- 20e siècle.; Santé publique -- Cuba -- Histoire -- 20e siècle.; Politique sanitaire -- Cuba -- Histoire -- 20e siècle.; Cuba -- Histoire -- 1895-; Cuba -- Politique et gouvernement -- 1895-; SOCIAL SCIENCE / Ethnic Studies / Caribbean & Latin American Studies; Tuberculosis; Public health; Politics and government; Medical policy; Cuba; Social services & welfare, criminology; Health and Wellbeing; Since 1895; History